Implementasi Program Pelayanan Dokumen Kependudukan Secara Online di Nagari Binjai Kacamatan Tigo Nagari Kabupaten Pasaman - Sonia Fitri, Yola; Malau, Hasbullah (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research describes implementing the online population document service program in Nagari Binjai, Tigo Nagari District, Pasaman Regency. The background of this research is that many people in Nagari Binjai still have not renewed their population documents and still take care of documents directly at the Disdukcapil of Pasaman Regency. The type of research is qualitative with a descriptive approach. Interviews and documentation studies obtained data. This research uses Edward III's theory, which focuses on communication, resources, disposition, and bureaucratic structure. Of the four indicators, three have not run optimally, namely communication, resources, and disposition, while one indicator, namely the bureaucratic structure, has run well. In the communication indicator, the program's implementation has yet to be effective because the community still needs to gain more knowledge of the information conveyed by the online service program organizers. The resources available for implementing the program in Nagari Binjai are minimal, with only one person involved, and financial resources still need a particular budget allocation for this service. The attitude of implementers in the online service program in Nagari Binjai reflects a democratic attitude but still lacks the commitment needed to carry out their duties and functions correctly.